2022
DOI: 10.1371/journal.pone.0270507
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in breast cancer cases following chemotherapy: A pre and post observational study in a tertiary hospital in Yogyakarta, Indonesia

Abstract: Objectives To observe pre- and post-treatment vitamin D level and its association with treatment and concomitant factors in breast cancer patients treated with chemotherapy. Methods We performed a pre-post observational analysis that nested in an ongoing prospective cohort study of breast cancer patients at Dr. Sardjito General Hospital, Yogyakarta, Indonesia. 136 subjects were recruited from the main study. Information on subjects’ socio-demographic characteristics clinical status, and tumour profile was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
(68 reference statements)
1
5
0
Order By: Relevance
“…The daily vitamin D 3 was more efficacious than weekly and monthly administrations ( 59 ). These finding was consistent with the Endocrine Society that the vitamin D could only perform its function when serum 25(OH)D levels reached 30 ng/mL (75 nmol/L) or higher ( 36 , 38 ). Vitamin D has major effects on both the innate and adaptive immune systems through its biological activities ( 12 , 27 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The daily vitamin D 3 was more efficacious than weekly and monthly administrations ( 59 ). These finding was consistent with the Endocrine Society that the vitamin D could only perform its function when serum 25(OH)D levels reached 30 ng/mL (75 nmol/L) or higher ( 36 , 38 ). Vitamin D has major effects on both the innate and adaptive immune systems through its biological activities ( 12 , 27 ).…”
Section: Discussionsupporting
confidence: 90%
“…Another study by Chillon et al found that 25(OH)D levels did not correlate with anti-SARS-CoV-2 IgG levels in healthy subjects with deficient vitamin D status [median 25(OH)D levels less than 30 ng/mL (75 nmol/L)] during four sequential measurements ( 66 ). However, vitamin D could only perform its function when blood 25(OH)D serum levels exceeded 30 ng/mL (75 nmol/L) ( 36 , 38 ). In our study, the median 25(OH)D level was 36.36 ng/mL (90 nmol/L), indicating that the subjects had sufficient vitamin D status ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In consistent with our study, Chel et al [ 32 ], evaluated the vitamin D status of oral Vit-D3 doses of 600 IU/day, 4,200 IU/week, and 18,000 IU/month, which shows that daily consumption of vitamin D has more impact than weekly or monthly consumption [ 32 ]. Their findings were consistent with the Endocrine Society’s conclusion that serum vitamin D levels of 30 ng/mL (75 nmol/L) or higher can boost the immune system [ 33 ]. Vit-D3 has important effects on both the innate and adaptive immune systems belong its biological functions [ 34 ].…”
Section: Discussionsupporting
confidence: 84%